(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper deals with analysis of image Enhancement and background detection used in Mathematical Morphological [MM]. In this paper, Low intensity images have been processed through Block Analysis and Morphological Transformation. Basically, Weber‟s Law Operator is used to analyze Low intensity images which are carried out by two methods such as Image background detection by block analysis while second operator utilize opening by reconstruction to define multi background notion. Basic Morphological Transformations are like Erosion, Dilation, Compound operation such as Opening by reconstruction, Closing by Reconstruction and Block Analysis is used to detect the background of images. Analysis of above mention methods illustrated through the processing of images with filtering techniques along with different dark background images.